Development of a toolkit in Silverlight to detect physiognomies in real time - doi: 10.4025/actascitechnol.v35i1.13713 - Ghilardi, Marcelo Cabral; Ribeiro, Vinicius Gadis; Zabadal, Jorge Rodolfo; Poffal, Cristiana Andrade (Acta Scientiarum. Technology, 2012)
Security demands, forensic practices and the identification of criminals require the detection and recognition of iris and fingerprints and of faces in videos and photographs. Moreover, there is an increasing need for multiple forms of human-machine interaction. Control devices by body stimulus are a need and a trend. For example, currently some computers, laptops, phones and video games provide interaction from their cameras, not only for face detection but also for body movements and the detection of objects. Most devices are Internet accessed, which creates an even greater range of possibilities. These technological trends have prompted the development a toolkit for detecting faces in real time. The choice of Silverlight framework for the development of this toolkit provides these applications with instruments that could be implemented in a web browser. This toolkit may be used for other purposes, such as face and iris recognition, body movement and the monitoring of premises. An application was developed as example and proof of concept. Â